“I know I can, but I don't fit” : perceived fit, self-efficacy, and entrepreneurial intention - Hsu, Dan K. (2020)
While extant literature generally suggests a positive relationship between entrepreneurial self-efficacy and entrepreneurial intention, several moderators have been identified – suggesting possible boundary conditions on that relationship. This paper introduces perceived person-entrepreneurship fit to entrepreneurship and shows that it moderates the relationship between entrepreneurial self-efficacy and entrepreneurial intention. Three studies are conducted which illuminate the utility of randomized experiments and methodological approaches to address limitations in the interpretation of empirical results. Studies 1 and 2 are randomized experiments to examine causality; Study 3 contains two correlational surveys to triangulate the results by examining whether the proposed effects withstand the influence of confounding variables in real-life. The findings indicate that when a strong perception of fit with entrepreneurship is achieved, entrepreneurial intention is strongly predicted by entrepreneurial self-efficacy. In contrast, if one perceives a low level of fit or no fit, entrepreneurial intention will be low, regardless of entrepreneurial self-efficacy.